1992
DOI: 10.1055/s-2007-1021269
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Systolic and Diastolic Cardiac Function after Prolonged Aerobic Exercise in Healthy Subjects

Abstract: We studied 11 healthy untrained volunteers (aged 28.9 +/- 4.6 years) during 60 minutes of aerobic ergometric exercise with constant heart rates of 130 to 140 beats/minute. We found a continuous and significant decrease in systolic and diastolic pressure from 175 +/- 18/77 +/- 7 mmHg in the 5th minute to 144 +/- 14/68 +/- 6 mmHg in the 60th minute of exercise. Cardiac function and structure were assessed by M-mode echocardiography before exercise, after 5 minutes and after 60 minutes of exercise at comparable h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
2
18
1
1
Order By: Relevance
“…In contrast with previous reports [1][2][3][20][21][22][23], our study did not show any significant change in systolic function after both competitions as well as in between the two races. Additionally, cardiac enzymes were within normal values after both races, confirming that no myocardial damage occurred in any athlete, as outlined by a previous study [24].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with previous reports [1][2][3][20][21][22][23], our study did not show any significant change in systolic function after both competitions as well as in between the two races. Additionally, cardiac enzymes were within normal values after both races, confirming that no myocardial damage occurred in any athlete, as outlined by a previous study [24].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown that trained athletes may develop different degrees of systolic and diastolic dysfunction following strenuous exercise [1][2][3][20][21][22][23]. These studies, which employed two-dimensional Doppler echocardiography, have shown transient left ventricular systolic and diastolic dysfunctions soon after prolonged exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Distance/duration Measurement technique Timing of measurement Position/recovery or exercise data Observations Douglas et al [11] Ironman Triathlon 2D echo 3-19 min post-exercise Supine/recovery EF, FS (segmental) Douglas et al [12] Ironman Triathlon Doppler echo 20 min post-exercise Supine/recovery EDD Douglas et al [10] Ironman Triathlon Doppler echo 3-23 min post-exercise Supine/recovery EDD, FS, Ketelhut et al [13,17] 60 min cycling M-mode echo Immediately after 5 min and 60 min of exercise Supine/exercise SV, Q, EF, FS ; ESD Lucı! a et al [21] Marathon (42 km) M-mode and Doppler echo Immediately before and after exercise, and after 24-36 h of recovery Supine/recovery EF, mV CF during recovery (vs. preexercise) ; E/A ratio Niemela$ et al [8] 24 h run M-mode echo Immediately to 25 min postexercise Supine/recovery EDD, ESD, FS, mV CF Niemela$ et al [9] 24 h run M-mode echo Immediately post-exercise Supine/recovery FS, DFR, EDD, Palatini et al [20] 50 min cycling M-mode echo During exercise at 10 min intervals [4][5][6].…”
Section: Studymentioning
confidence: 99%
“…It remains unclear if LV dysfunction during such activity contributes to the decrease in stroke volume. Some investigations have described an impairment of LV function following exercise of a prolonged nature [8][9][10][11][12][13][14][15]. It is possible that a decline in ventricular output involves a depression in the contractile state ; however, despite reports of a transient decline in systolic function [8][9][10][11][12][13][14]16,17] and diastolic filling characteristics [9,13,16], several studies have failed to report a decline in LV performance [18][19][20][21].…”
Section: Studymentioning
confidence: 99%
“…The EICF is found in both well trained (Douglas et al 1987;Whyte et al 2000) and untrained subjects (Seals et al 1988;Vanoverschelde et al 1991;Ketelhut et al 1992Ketelhut et al , 1994Palatini et al 1994), but subjects of disparate training background within the same experimental design have not been compared. This study evaluated whether the continued increase in HR during prolonged exercise becomes manifested in response to altered preload to the heart or to EICF and/or myocardial damage as indicated by serum cTnT in healthy young males encompassing a range of maximal oxygen uptake ( _ V O 2maz ).…”
Section: Introductionmentioning
confidence: 99%